Brain responses to bladder filling in older women without urgency incontinence12. Issue 5 (8th March 2013) - Tadic, Stasa D.; Tannenbaum, Cara; Resnick, Neil M.; Griffiths, Derek
Abstract Aims To investigate normal brain responses to bladder filling, especially when there is little or no sensation as in much of daily life. Methods We performed an functional magnetic resonance imaging (fMRI) study of brain responses to bladder filling in normal female subjects, evoked by infusion and withdrawal of fluid in and out of the bladder. Using the contrast (infusion–withdrawal), we imaged brain activity at small bladder volumes with weak filling sensation and also with full bladder and strong desire to void. Results Eleven women, average age 65 years (range: 60–71 years) were included. With full bladder and strong desire to void, filling provoked a well‐known pattern of activation near the right insula and (as a trend) in the dorsal anterior cingulate cortex and supplementary motor area. There was no significant deactivation. With small bladder volume filling provoked widespread apparent deactivation and no significant activation. Apparent deactivation was associated with increased fMRI signal during withdrawal rather than decrease during infusion, suggesting artifact. A correction for global changes in cerebral blood flow eliminated it and revealed significant subcortical activation, although none in frontal or parietal cortex. Conclusions In older women with normal bladder function, infusion into an already full bladder resulted in strong sensation and brain activation near the insula and in the dorsal anterior cingulate/supplementary motor complex. With near‐empty bladder and little sensation, the situation during much of daily life, these cortical areas were not detectably activated, but activation in midbrain and parahippocampal regions presumably indicated unconscious monitoring of ascending bladder signals. Neurourol. Urodynam. 32: 435–440, 2013. © 2013 Wiley Periodicals, Inc.